Mathematics
AzaleeFelzien147
6

Please help me solve this i have no idea What value of x satisfies the equation 3(x – 4) + 12(x – 9) = 4x + 13? Here is the choices, please explains how you got it. -9 8/11 2 4/11 12 1/11 -5 13/19

+0
(1) Answers
SunnyDragotta955

Simplify both sides of the equation 3(x-4)+12(x-9)=4x+13Distribute (3)(x)+(3)(-4)+(12)(x)+(12)(-9)=4x+133x+-12+12x+-108=4x+13Combine like terms 15x+-120=4x+1315x-120=4x+13Subtract 4 from both sides15x-120-4x=4x+13-4x11x-120=13Add 120 to both sides 11x-120+120=13+12011x=133Divide both sides by 1111x/11=133/11x=133/11 or x= 12 1/11 I hope that's help !

Add answer